2020
DOI: 10.4103/jrms.jrms_345_19
|View full text |Cite
|
Sign up to set email alerts
|

Could preoperative sonographic criteria predict the difficulty of laparoscopic cholecystectomy?

Abstract: Background: Although laparoscopic cholecystectomy (LC) is the gold standard approach for gallbladder diseases, this sometimes may face difficulties and require conversion to open surgery. The preoperative ultrasonographic study may provide information about the probability of difficult LC, but the data in this term are uncertain. We assessed the value of preoperative ultrasonographic findings for the prediction of LC's difficulty. Materials and Methods: The current pros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 27 publications
0
5
0
Order By: Relevance
“…In this study, only patients with symptomatic cholelithiasis who underwent elective LC were included. Patients with acute cholecystitis, pancreatitis, or obstructive jaundice were excluded because these are well‐known risk factors for difficult LC, and this is similar to what was reported previously 15,16,21 …”
Section: Discussionmentioning
confidence: 63%
See 1 more Smart Citation
“…In this study, only patients with symptomatic cholelithiasis who underwent elective LC were included. Patients with acute cholecystitis, pancreatitis, or obstructive jaundice were excluded because these are well‐known risk factors for difficult LC, and this is similar to what was reported previously 15,16,21 …”
Section: Discussionmentioning
confidence: 63%
“…Patients with acute cholecystitis, pancreatitis, or obstructive jaundice were excluded because these are well-known risk factors for difficult LC, and this is similar to what was reported previously. 15,16,21 Several studies have investigated the ultrasonographic features that could predict difficult LC and most of them agreed that a thickened GB wall was one of the risk factors for difficult LC. [14][15][16][17]22 In our study, GB wall thickness of more than 4 mm was a significant risk factor for difficult LC according to G10 cholecystitis severity score in the univariate analysis.…”
Section: Discussionmentioning
confidence: 99%
“…[75][76][77] Although equipment failure is known to be a preventable cause of conversion, 78 it is still a significant indication for conversion in Africa and other developing settings. 7,25,79,80 This is unlike in developed settings where it was reported mainly in the 1990s and early 2000s. 81,82 Proper training, maintenance of laparoscopic instruments and materials, and proper imaging investigations would serve as solutions to reduce the rate of conversion.…”
Section: Discussionmentioning
confidence: 89%
“…Studies from other settings have also reported adhesions and hemorrhage to be a major cause of conversion 75–77 . Although equipment failure is known to be a preventable cause of conversion, 78 it is still a significant indication for conversion in Africa and other developing settings 7,25,79,80 . This is unlike in developed settings where it was reported mainly in the 1990s and early 2000s 81,82 .…”
Section: Discussionmentioning
confidence: 99%
“…A previous study by Khan et al involving 5136 patients reported that patients with stones impacted in Hartmann's pouch had higher incidence of AC, gallbladder empyema, and Mirizzi syndrome, higher grades of operative difficulty but similar postoperative complications [13]. A study by Jalil et al also found stone impaction to be the single most important ultrasound finding to predict difficulty of LC [14]. A French study involving 420 patients found male gender, history of AC, absolute neutrophil count, serum fibrinogen, and alkaline phosphatase levels to be predictive of difficult LC [15].…”
Section: Discussionmentioning
confidence: 96%